Peran Kepala Sekolah dalam Meningkatkan Mutu Kegiatan Ekstrakurikuler di Madrasah Darulhuda Wittaya Provinsi Yala Thailand Selatan Tahun 2015-2016 - Vateh, Mr. Adnan; , Drs. M. Yusron, M.Ag (2016)
Based on the importance of the role of extracurricular activities for the school, then the effective supervision must be made by the principal, so that the activities those have been planned and executed can be achieved in accordance with the intended and desired school purpose by schools, like, to develop the potentials of learners through extracurricular activities, either social or religius. Empirical reality on the ground did show that the proportion of extracurricular activities are not in balance, lack of attention, and even tend to be overlooked. School leaders to perform tasks of leadership should understand their role as leaders for improving education personnel in extracurricular. Thus, the extracurricular activities will develop well if the principal contribute to its development, particularly in the area of oversight. Thus, the study of the principal's role in improving the quality of extracurricular activities at Madrasah Darulhuda Wittaya South Thailand Yala Province may be one of the considerations in the development of extra-curricular activities. The research aims to identify and understand the performance of principals in improving the quality of extracurricular activities at Madrasah Darulhuda Wittaya southern Thailand Yala Province. This study is a field research, which is directly applied in the real life, specifically in what is happening. The study was conducted in communities Wangpaya southern Thailand Yala Province. The data collection method of this research is observation, interview, and documentation. The development of quality of extracurricular activities at Madrasah Darulhuda Wittaya southern Thailand Yala Province has been executed well, based on the implementation of quality development in the aspects: Professional Development of Teachers and Coaches, Delegation, Administration Management, Providing Help, Communication, Innovation, Awarding. But in the monitoring and control, the principal less perform well because the supervision is only checked extracurricular activitiesreports once per month. The development of quality of extracurricular activities at Madrasah Darulhuda Wittaya is influenced by supporting and inhibiting factors. The supporting factors, among others, are the availability of an adequate place with an area of 7 ha, and complete infrastructure. The inhibiting factors, among others: are lack of funding for delegate and salaries, and less competency of the quality of teachers. Keywords: Principal, Extracurricular